Naturalizing Epistemology - D'Agostino, F. author. aut Link
VIII, 216 p. 4 illus.
Keywords: In identifying that the 'essential tension' is the balance between conservative and innovative approaches in the development of knowledge - tried-and tested or new directions - Kuhn pointed out that these two attitudes are both appropriate. This study adds to this picture the social and psychological dynamics that underpin any such balancing.